Legal nature and the criminal law effect: Substantive and procedural: Of statute of limitations of criminal prosecution - Škulić Milan (Anali Pravnog Fakulteta u Beogradu)
The article contains an analysis of criminal justice and criminal effects of Statute of Limitations of Criminal Prosecution, as well as institute which has double natures, i.e. it is the institute of substantial criminal law and as well the institute of procedural criminal law, which has its own specific action in criminal proceedings. The Statute of Limitations of Criminal Prosecution is a permanent criminal procedural obstacle which prevents the prosecution and is cause for termination of the criminal proceedings if he started, and prevents its start, if criminal proceedings are not initiated, which is in both of these situations manifested by adopting the relevant decisions of the proceeding - by the criminal court or by a public prosecutor, in case of criminal offenses which are prosecuted ex officio. In the article are discussed the concept of statute of limitations of criminal prosecution and its ratio legis, certain comparative solutions (German criminal law and criminal law of the United States of America), the normative solutions in the present Serbian criminal law, as well as basic criminal procedural effects of statute of limitations of criminal prosecution with a special analysis some illogical solutions in the Criminal Procedure Code of Serbia, where statute of limitations of criminal prosecution is wrongly classified as one of the absolutely essential violations of criminal procedure.